Homecoming as displacement: An analysis from the perspective of returning social scientists. (January 2014) - Bielsa, Esperança; Casellas, Antònia; Verger, Antoni
International mobility is a growing phenomenon in which academicians are highly represented. While studies on transnationalism have widely focused on the mobility of people in terms of migrancy and exile, homecoming has been much less studied. This article contributes to filling this gap by analysing the homecoming experiences of three social scientists who have coincided in a Catalan university. The narrative of their personal trajectories and experiences of return allows for an understanding of homecoming in relation to wider discourses of mobility in the context of globalization. Contrary to dominant beliefs, homecoming is approached not as a return to one's origins, but as a movement that implies dislocation and displacement and puts the homecomer in a position that is, in important ways, not essentially dissimilar to that of the stranger. The authors argue that the study of homecoming sheds light on certain neglected aspects of contemporary globalization, such as the existential limits to the international mobility of people or the favouring of local attachments over global options combined with the prevalence of cosmopolitan orientations. The article also calls attention to the cultural transfers of returnees to their countries of origin as well as to their world-making activities.